American Time Use Survey (ATUS), 2009 ([Verlag nicht ermittelbar], 2012)
The American Time Use Survey (ATUS) collects information on how people living in the United States spend their time. Data collected in this study measured the amount of time that people spent doing various activities in 2009, such as paid work, child care, religious activities, volunteering, and socializing. Respondents were interviewed only once about how they spent their time on the previous day, where they were, and whom they were with. Part 1, Activity File, includes additional information on activities in which respondents participated, including the location of each activity and the total time spent on secondary child care. Part 2, Call History File, gives information about each call attempt. Part 3, Case History File, contains information about the interview process. Part 4, ATUS-CPS 2009 File, contains demographic and occupational data on respondents and members of their household collected during their participation in the Current Population Survey (CPS). Part 5, Respondent File, contains demographic information about respondents. Part 6, Roster File, contains information about household members and non-household children under the age of 18. Part 7, Activity Summary File, contains a summary of the total amount of time they spent doing each activity that day. Part 8, Trips File, provides information about the number, duration, and purpose of overnight trips away from home for two or more nights in a row in a given reference month. Part 9, ATUS 2009 Replicate Weights File, contains base weights, replicate base weights, and replicate final weights for each case that was selected to be interviewed for the ATUS. Part 10, Who File, includes data on who was present during each activity. Demographic variables include sex, age, race, ethnicity, marital status, education level, income, employment status, occupation, citizenship status, country of origin, labor union membership of household members, and household composition.